THE FACTORS AFFECTING THE LEVEL OF TOURIST SATISFACTION USING TRAVEL AGENTS AND DESTINATIONS OF CHOICE: CASE STUDY IN BALI - Suwena, I Ketut; Arismayanti, Ni Ketut (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 1 (2022): Jurnal IPTA (July 2022)DO - 10.24843/IPTA.2022.v10.i01.p15, 2022)
Nowadays, tourism is a common thing done by anyone. In the digital era, there is a shift of tourists in traveling in terms of the use of travel agents in planning their trips. There are tourists who plan their trips independently and there are also tourists who continue to use travel agents in traveling. The level of satisfaction of tourists in using the services of travel agents and destinations that tourists choose to travel is important to know the factors that influence the level of tourist satisfaction. This study aims to determine and analyze the factors that influence the level of satisfaction of tourists in using travel agents and choosing tourism destinations. This research was conducted in Bali by distributing questionnaires to tourists and interviewing informants. Data collected techniques with observation, interviews, questionnaires, literature study. The data analysis technique uses descriptive qualitative, factor analysis, and Likert Scale technique. The number of samples was 400 tourists, consisting of 200 domestic tourists and 200 overseas tourists. The results of this study are expected to be used as a basis for evaluation and policy making for the government in tourism as an effort to increase the level of satisfaction and loyalty of tourists who travel to Bali.